Analisis Penutupan Hutan sebagai Taksiran Deforestasi: Suatu Model Ekonometrika - Tjandrakirana, Roosi; Tambunan, Mangara (Jurnal Ekonomi dan Pembangunan Indonesia, 2006)
Deforestation speed was increasing fastly from 1,87 million ha/year on the 1985-1997 period to 2,6 million ha/year on 1998-2000 period. This increase in speed cause many problems such as: a decrease in environment quality, the drastic decrease in forest timber production which affects timber supply, etc. There are many factors affecting a change in the forest coverage. At first, management of Forest Utilization Right (HPH) and the development of timber industry are perceived as the cause of the increase in deforestation speed. However, there are other argument that propose an increase in the number of farmers and nomad farmer in forest area as the cause the change in forest coverage. The purpose of this study is to get a picture of the direct cause of the change in forest coverage. This study use panel data method for 19 provinces from 1976 to 2000. The results show that there is a positive relationship between speed of deforestation and forest coverage. Logging activity and forest conversion contribute to the change in forest coverage where forest conversion has bigger impact on the speed of deforestation. This analysis indicates that forest conversion is the m'!ior cause of deforestation in Indonesia. The conversion of forest into plantation is the mqior cause of deforestation in Indonesia. On the other hand, the number of small/armers or people live in forest area has very little impact on deforestation.